Use of BIM approach to enhance construction interface management: a case study - Lin, Yu-Cheng (Journal of Civil Engineering and Management, 2015)
Many interface events and problems occur during the construction phase of construction projects, such that tracking and controlling these are essential to construction management. Interface management (IM) has become the most important aspect of a sound project management strategy. IM affects project cost, scheduling, and quality both directly and indirectly in construction projects. Interface or changed events can be identified and tracked using IM, such that construction processes can be improved, while minimizing rework and reducing total project duration. Despite the many studies and discussions in academic and practical literature, systematic approaches and information platforms for managing interface events and problems during the construction are lacking. This study tracks and manages interface events using novel three-dimensional (3D) interface maps integrated into the building information modelling (BIM) approach. The BIM approach, which is utilized to retain interface information in a digital format, facilitates easy interface updating and transfer in the 3D CAD environment. The 3D-based interface maps provide users with an overview of interface events during a given construction project, such that users can track and manage interfaces virtually. The primary purpose of this study is to develop a web Construction BIM-based IM (ConBIM-IM) system for engineers to enhance interface information sharing and efficiency tracking in construction projects. The ConBIM-IM system is applied to a case study of a building project in Taiwan to verify its efficacy and demonstrate its IM effectiveness. Case study results show that the ConBIM-IM system is effective for managing interfaces using the BIM approach in construction.